Macular morphometrics in foveal displacement following full thickness macular hole surgery - Nair, Unnikrishnan (Indian J Ophthalmol, 2020)
PURPOSE: To investigate if the ratio of the preoperative nasal and temporal “arms” of the macular hole (MH) can have a predictive value in the magnitude of foveal displacement postoperatively. METHODS: This is retrospective interventional case series of eyes of 40 patients with full-thickness macular hole (FTMH), which underwent vitrectomy with internal limiting membrane (ILM) peeling and had Type 1 closure.All subjects underwent pre and postoperative optical coherence tomography (OCT, Heidelberg, Spectralis, Germany). Their pre and postoperative foveo-papillary distance (FPD) was measured and the magnitude of shift was calculated. The nasal and temporal arm lengths, their ratio (N/T ratio), and the hole base diameter were measured in the preoperative OCTs.The main outcome measure was the correlation of the N/T ratio with the postoperative foveal displacement. RESULTS: We observed that in 25% (n = 10) the fovea shifted temporally; in 75% (n = 30) it shifted nasally. The shift did not show a significant correlation with either N/T ratio (r = 0.155, P = 0.34) or with base diameter (r = -0.008, P = 0.961). The odds ratio (OR) was 4.92 (P = 0.04) and the relative risk (RR) was 3.12 (P = 0.039) for a longer temporal segment to predict a temporal shift. CONCLUSION: Both nasal and temporal shifts are possible after successful hole closure and temporal shifts can also occur in a significantly high proportion of patients. Temporal shifts are more likely in eyes with a longer temporal segment.